Expert System for Diagnosing Gastric Disease Using the Forward Chaining Method - Andriani, Tuti; Mentari, Risca Sri; Situkkir, Meiarni; Nasution, Darmeli (Cattleya Darmaya Fortuna, 2024)
Health is the most crucial aspect of life, as it signifies a state of well-being and vitality. Gastric diseases pose a significant health concern, often requiring prompt and accurate diagnosis for effective treatment. In this study, an expert system utilizing the forward chaining method is developed to aid in diagnosing gastric diseases. The system aims to streamline the diagnostic process, providing users with timely and reliable results to facilitate early intervention and management of stomach disorders. Through the integration of technology and medical expertise, this system offers a valuable tool in enhancing healthcare delivery and improving patient outcomes in the realm of gastric health. The research findings highlight the effectiveness of an expert system employing the forward chaining method in diagnosing gastric diseases. The system demonstrates the capability to efficiently identify and assess symptoms related to stomach disorders, offering users a reliable and accessible platform for obtaining accurate diagnostic results. By leveraging current knowledge base rules and user-provided symptom data, the system enhances the diagnostic process, potentially reducing both time and costs associated with diagnosing gastric diseases. This study underscores the significance of technological advancements in healthcare, particularly in the realm of gastric health, by providing a valuable tool for early detection and management of stomach disorders.